Zróżnicowanie przestrzenne niepielęgnowanych drzewostanów brzozy brodawkowatej (Betula pendula L.) odnowionych sadzeniem - Szmyt, Janusz; Korzeniewicz, Robert (Leśne Prace Badawcze, 2012)
The aim of this paper was to describe changes in the spatial distribution of living trees in planted and untended birch stands, as well as to determine the spatial differentiation of the diameters and height of their constituent trees Analysis was performed in 9 and 39-year old stands. The structural diversity of birch stands was described using the following spatial indices: Clark-Evans index (CE), spatial differentiation index for DBH (TD) and height (TH). The CE index describes the horizontal distribution of trees within a stand and the TD/TH indices indicate the size differentiation between neighbouring trees within a stand (DBH and H, respectively). The indices mentioned above concern small spatial scales. Our results indicate a regular spatial distribution of living trees on the ground at age nine, shown by high values of CE index. After 30 further years of stand development CE values were distinctly lower and no longer significantly different from the value for a random distribution of trees. At age 39, the 2 stands had a random spatial distribution and in the planted stand living trees still retained a regular spatial arrangement. Analyzing the spatial differentiation of diameter and height of trees revealed that there was little differentiation between neighbours in forest stands in neither their diameter and height. The highest average values for the TD index decreased for stands during the 30 years since there initial measurement at age nine. A similar trend was observed for height differentiation (TH), which decreased from a maximum at age nine